(untitled) (Fiep Bulletin - online, 2013)
This study aims to understand the different meanings of the program activities Live Better Age, the City of Volta Redonda - RJ from the speeches of older practitioners. It is important to do research that can contribute to improving public policy of this population segment, encouraging more investments and allowing for better intervention. To try to unravel the representations that surround the aging of the attendees of this program, we deepen our look at the theory of Pierre Ansart (1978). Methodology: This is a qualitative research, a case study. For this, we apply a semi-structured interview that was analyzed from the perspective of discourse analysis of Eni Orlandi (2006). We interviewed 11 subjects, of both sexes, in two places where they occur the program classes. Conclusion: This study demonstrates that adherence to Live the Best Age Program is more than a quest for health care, living, socializing or occupation. Attending classes is able to exercise citizenship in society, is able to take care to keep physically autonomous. The space of the classroom is a place that enables the exchange of experiences, there, you can hear the problems of others and relationships become equal, without prejudice and without discrimination.